The Development of Management Model for Processed Agricultural Products to Enhance Value for The Khao Yai Nature Community Enterprise - Ruktanatuch, Kittana; Ruktanatuch, Tanont; Ruktanatuch, Siraphob (Journal of Cultural Analysis and Social Change, 2026)
This study aimed to: 1) Examine the current conditions and the factors affecting the management of processed agricultural products of the Khaoyai Thammachat Community Enterprise, 2 ) Analyze appropriate approaches and practices for enhancing management efficiency, 3) Develop and present a management model that corresponds to the context of the community enterprise, and 4) Test and evaluate the effectiveness of the developed model. The population of the study consisted of 10 members of the community enterprise, selected through purposive sampling. The research employed a mixed-methods approach, and the instruments used for data collection included in-depth interviews and a 5-point rating scale questionnaire. Data analysis utilized descriptive statistics, namely mean and standard deviation, SWOT analysis, and paired t-test. The results revealed that 1) The current conditions of the management of processed agricultural products were overall at a high level, with a mean of 3.89 and a standard deviation of 0.49. When considering each aspect, competitiveness had the highest mean (4.00), followed by production technology (3.94), and management and human resources (3.86). 2) The SWOT analysis indicated that the strengths of the community enterprise included trustworthy leadership and the use of resources that reflect local identity, while the weaknesses were the lack of a systematic business plan and limited knowledge of production and marketing technologies. 3 ) The developed management model resulted from synthesizing SWOT information together with best practices, aiming to address structural problems and support longterm capacity development. and 4) Sixty percent of the members showed improved operational capability, and post-training knowledge scores increased significantly according.